2020
DOI: 10.1016/j.tranon.2019.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Small-Molecule Dual PLK1 and BRD4 Inhibitors are Active Against Preclinical Models of Pediatric Solid Tumors

Abstract: Simultaneous inhibition of multiple molecular targets is an established strategy to improve the continuance of clinical response to therapy. Here, we screened 49 molecules with dual nanomolar inhibitory activity against BRD4 and PLK1, best classified as dual kinase-bromodomain inhibitors, in pediatric tumor cell lines for their antitumor activity. We identified two candidate dual kinase-bromodomain inhibitors with strong and tumor-specific activity against neuroblastoma, medulloblastoma, and rhabdomyosarcoma t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 55 publications
0
16
0
Order By: Relevance
“…Inhibitors of PLK1 , such as BI6727 and BI2356, preferentially trigger apoptosis of MYCN -amplified neuroblastoma and small cell lung cancer, and this therapeutic efficacy is synergistically enhanced by combined use with antagonists of anti-apoptotic B cell lymphoma 2 (BCL2) ( 128 ). UME103 and 9b, two novel dual PLK1 and BRD4 inhibitors, show better antitumor activity by inhibiting the transcription of MYCN gene and promoting the degradation of N-MYC protein ( 129 , 130 ).…”
Section: Regulation Of N-myc Stabilitymentioning
confidence: 99%
“…Inhibitors of PLK1 , such as BI6727 and BI2356, preferentially trigger apoptosis of MYCN -amplified neuroblastoma and small cell lung cancer, and this therapeutic efficacy is synergistically enhanced by combined use with antagonists of anti-apoptotic B cell lymphoma 2 (BCL2) ( 128 ). UME103 and 9b, two novel dual PLK1 and BRD4 inhibitors, show better antitumor activity by inhibiting the transcription of MYCN gene and promoting the degradation of N-MYC protein ( 129 , 130 ).…”
Section: Regulation Of N-myc Stabilitymentioning
confidence: 99%
“…Moreover, our model predicted that PFI-1 might show cross-activity with a range of kinases. Because an increasing number of studies have shown that BRD4/BET inhibitors and kinase inhibitors might act synergistically in a range of cancer types (Sun et al, 2015), the predicted offtarget interactions with kinases might provide clues and starting points for further study of related dual functional inhibitors (Timme et al, 2020). In some cases, the predictions were unsuccessful, e.g., ATM and RAD3-related (ATR) kinase is a reported target of VE-821, but this target was ranked at the 1594th position.…”
Section: Model Verification Using Lincs Phase II Datamentioning
confidence: 99%
“…Polo-like kinase 1 inhibitors are enzyme PLK1 antagonists. They lead to cell cycle arrest through canceling phosphorylated MYC protein stability via occluding its binding to PLK1 [ 163 ]. Both compounds have similar properties: they decrease proliferation and self-renewal, diminish cell viability, induce apoptosis, and exempt tumor expansion in HD-MB03, Daoy, UW228, and ONS-76 cell lines.…”
Section: Epigenetic Therapeutics In Medulloblastomamentioning
confidence: 99%
“…For this reason, a recent discovery of dual BRD4/PLK1 inhibitors has appeared to be an attractive alternative. Among these compounds, UMB103 and UMB160 are characterized with selective antitumor activity concomitantly with a minor impact on properly functioning cells [ 163 ]. It was evinced via UMB103 and UMB160 application on MYC -amplified HD-MB03 line cells, which has contributed to reduced MYC and MYCN expression, proliferation, and cell viability simultaneously with enhanced apoptosis [ 163 ].…”
Section: Epigenetic Therapeutics In Medulloblastomamentioning
confidence: 99%
See 1 more Smart Citation